From Monitors to Monitors: A Primitive History - Troy Astarte (Minds and Machines, 2024)
As computers became multi-component systems in the 1950s, handling the speed differentials efficiently was identified as a major challenge. The desire for better understanding and control of ‘concurrency’ spread into hardware, software, and formalism. This paper examines the way in which the problem emerged and was handled across various computing cultures from 1955 to 1985. In the machinic culture of the late 1950s, system programs called ‘monitors’ were used for directly managing synchronisation. Attempts to reframe synchronisation in the subsequent algorithmic culture pushed the problem to a higher level of abstraction; Dijkstra’s semaphores were a reaction to the algorithms’ complexity. Towards the end of the 1960s, the culture of ‘structured programming’ created a milieu in which Dijkstra, Hoare, and Brinch Hansen (among others) aimed for a concurrency primitive which embodied the new view of programming. Via conditional critical regions and Dijkstra’s ‘secretaries’, the co-produced ‘monitor’ appeared to provide the desired encapsulation. The construct received embodiment in a few programming languages; this paper ends by considering Modula and Concurrent Pascal.